2018
DOI: 10.1084/jem.20171905
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic post-conditioning promotes hematoma resolution via AMPK-dependent immune regulation

Abstract: Spontaneous intracerebral hemorrhage (ICH) produces the highest acute mortality and worst outcomes of all stroke subtypes. Hematoma volume is an independent determinant of ICH patient outcomes, making clot resolution a primary goal of clinical management. Herein, remote-limb ischemic post-conditioning (RIC), the repetitive inflation-deflation of a blood pressure cuff on a limb, accelerated hematoma resolution and improved neurological outcomes after ICH in mice. Parabiosis studies revealed RIC accelerated clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 85 publications
(101 reference statements)
2
61
0
Order By: Relevance
“…The RLCinduced beneficial effect was eliminated in mice that received CCR2-deficient monocytes, demonstrating a critical role of CCR2 ϩ monocytes for RLC-induced functional benefits. Consistent with our observation, a recent study addressing RLC effect in hemorrhagic stroke also showed that RLC-enhanced hematoma resolution was abolished in the absence of myeloid cells (Vaibhav et al, 2018), further supporting the role of circulating immune cells for the RLC-induced protective mechanism. One limitation of CCR2 KO adoptive transfer experiments is that we did not fully deplete CCR2 ϩ monocytes from the host mice.…”
Section: Discussionsupporting
confidence: 91%
“…The RLCinduced beneficial effect was eliminated in mice that received CCR2-deficient monocytes, demonstrating a critical role of CCR2 ϩ monocytes for RLC-induced functional benefits. Consistent with our observation, a recent study addressing RLC effect in hemorrhagic stroke also showed that RLC-enhanced hematoma resolution was abolished in the absence of myeloid cells (Vaibhav et al, 2018), further supporting the role of circulating immune cells for the RLC-induced protective mechanism. One limitation of CCR2 KO adoptive transfer experiments is that we did not fully deplete CCR2 ϩ monocytes from the host mice.…”
Section: Discussionsupporting
confidence: 91%
“…The inflammatory mediators released post-TBI not only alter the residential CNS cells, but also recruit peripheral cells into the brain. These immune cells polarize toward pro-or anti-inflammatory phenotypes due to surrounding signals from the tissue microenvironment [ 194 , 205 , 209 , 210 ]. In cortical impact TBI models, neutrophils are among the first cell types to respond to injury.…”
Section: Inflammationmentioning
confidence: 99%
“…These mechanisms may also activate mitochondrial ATP-sensitive potassium channels [ 309 ] that can restore the mitochondrial membrane potential and can suppress apoptosis following ischemia-reperfusion [ 310 ]. Recently, we reported that RIC improved hematoma resolution in a murine model of intracerebral hemorrhage (ICH) via modulation of AMP-activated protein kinase (AMPK) in macrophages [ 210 ]. RIC is gaining popularity, and more and more research has started focusing on this method in an effort to enhance endogenous protection [ 311 , 312 , 313 , 314 , 315 ].…”
Section: Inflammationmentioning
confidence: 99%
“…Notably, several papers showed that a main mechanism of action of MSCs from adipose tissue, is to promote tissue regeneration through M2 polarization [38][39][40], but hypoxia reduces their capability to polarize macrophages in the M2 phenotype [41] while for the PB-MNCs hypoxia is a physiological trigger for angiogenesis [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%